Characterization of Macrophages and Myofibroblasts Appearing in Dibutyltin Dichloride–Induced Rat Pancreatic Fibrosis. (April 2020) - Hashimoto, Ai; Karim, Mohammad Rabiul; Kuramochi, Mizuki; Izawa, Takeshi; Kuwamura, Mitsuru; Yamate, Jyoji
Macrophages and myofibroblasts are important in fibrogenesis. The cellular characteristics in pancreatic fibrosis remain to be investigated. Pancreatic fibrosis was induced in F344 rats by a single intravenous injection of dibutyltin dichloride. Histopathologically, the induced pancreatic fibrosis was divided into 3 grades (1+, 2+, and 3+), based on collagen deposition. Immunohistochemically, CD68-expressing M1 macrophages increased with grade and CD163-expressing M2 macrophages also increased later than M1 macrophage appearance. Double immunofluorescence showed that there were macrophages coexpressing CD68 and CD163, suggesting a possible shift from M1 to M2 types; similarly, increased major histocompatibility complex class II- and CD204-expressing macrophages were polarized toward M1 and M2 types, respectively. These findings indicated the participation of M1- and M2-polarized macrophages. Mesenchymal cells staining positive for vimentin, desmin, and α-smooth muscle actin (α-SMA) increased with grade. There were mesenchymal cells coexpressing vimentin/α-SMA, desmin/α-SMA, and glial fibrillary acidic protein (GFAP)/α-SMA; Thy-1-expressing immature mesenchymal cells also increased in fibrotic lesions. Because α-SMA expression is a reliable marker for myofibroblasts, α-SMA-expressing pancreatic myofibroblasts might be originated from GFAP-expressing pancreatic stellate cells or Thy-1-expressing immature mesenchymal cells; the myofibroblasts could simultaneously express cytoskeletal proteins such as vimentin and desmin. The present findings would provide useful information for analyses based on features of macrophages and myofibroblasts in chemically induced pancreatic fibrosis.